Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2174/0929867328666210902131021
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Type II Diabetes Chronic Complications: The Role of Polyphenols (Mini-Review)

Abstract: : The numerous complications of diabetes may be at least in part generated by the oxidative stress associated with the constant state of hyperglycemia. Polyphenols are plant based secondary metabolites that have high potentials in the prevention and treatment of some diseases, in particular those that involve oxidative stress, such as complications of diabetes. The purpose of this narrative review is to show the main evidence regarding the role of polyphenols in treating and preventing these complications. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The multitarget effects and broad spectrum of health benefits of polyphenols have pointed these compounds as promising therapeutic intervenients to fight the multiple complications of such complex diseases. In fact, in vitro and preclinical studies have shown that stilbenes, flavonoids (in particular, anthocyanins), and lignans slow the progression of kidney damage and prevent ischemic events and DN [ 48 ].…”
Section: Implication Of Polyphenols In Renal Pathophysiologymentioning
confidence: 99%
“…The multitarget effects and broad spectrum of health benefits of polyphenols have pointed these compounds as promising therapeutic intervenients to fight the multiple complications of such complex diseases. In fact, in vitro and preclinical studies have shown that stilbenes, flavonoids (in particular, anthocyanins), and lignans slow the progression of kidney damage and prevent ischemic events and DN [ 48 ].…”
Section: Implication Of Polyphenols In Renal Pathophysiologymentioning
confidence: 99%